Interglacial Antarctic–Southern Ocean climate decoupling due to moisture source area shifts - Landais A.; Stenni B.; Masson-Delmotte V.; Jouzel J.; Cauquoin A.; Fourre E.; Minster B.; Selmo E.; Extier T.; Werner M.; Vimeux F.; Uemura R.; et al. (Nature Geoscience, 2021)
Succession of cold glacials and warm interglacials during the Quaternary results from large global climate responses to variable orbital configurations, accompanied by fluctuating greenhouse gas concentrations. Despite the influences of sea ice and atmospheric and ocean circulations in the Southern Ocean on atmospheric CO2 concentrations and climate, past changes in this region remain poorly documented. Here, we present the 800 ka deuterium excess record from the East Antarctica EPICA Dome C ice core, tracking sea surface temperature in evaporative regions of the Indian sector of the Southern Ocean from which moisture precipitated in East Antarctica is derived. We find that low obliquity leads to surface warming in evaporative moisture source regions during each glacial inception, although this relative temperature increase is counterbalanced by global cooling during glacial maxima. Links between the two regions during interglacials depends on the existence of a temperature maximum at the interglacial onset. In its absence, temperature maxima in the evaporative moisture source regions and in East Antarctica were synchronous. For the other interglacials, temperature maxima in the source areas lag early local temperature maxima by several thousand years, probably because of a change in the position of the evaporative source areas.